Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Southern, Gulf, and Summer Flounder - Gilbert Carter R. (Washington U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.54)
Keywords: Fishes; History; Summer flounder; Gulf flounder; Southern flounder